Annual World Bank Conference on Development Economics--Regional 2007 : Beyond Transition - Bourguignon, François; Pleskovic, Boris (Washington, DC: World Bank, 2012)
This annual conference is a global gathering of the world's leading scholars and practitioners. Among the attendees are participants from developing countries, think tanks, NGOs, and international institutions. The papers included in this book concern issues such as: inequality and growth in transition; trade liberalization, inequality and poverty in Latin America and the Caribbean; can economic policy overcome geographic disadvantage in Eastern Europe and the Commonwealth of Independent States; and patterns of spatial convergence and divergence in India and China.